Deindividuation and antinormative behavior A meta-analysis. [article]. - Postmes, Tom
A meta-analytic integration reviews evidence for deindividuation theory as an explanation of collective and antinormative behavior. Deindividuation theories propose a subjective deindividuated state that causes transgression of general social norms. Deindividuation research classically manipulates anonymity, self-awareness, and group size. Results of 60 independent studies showed little support for (a) the occurrence of deindividuated (antinormative) behaviors or (b) the existence of a deindividuated state. Research results were explained more adequately by situation-specific than by general social norms. Analyses indicated that groups and individuals conform more to situation-specific norms when they are "deindividuated." These findings are inconsistent with deindividuation theory but support a social identity model of deindividuation effects. -- (from the author)